2011
DOI: 10.1007/s10600-011-0050-y
|View full text |Cite
|
Sign up to set email alerts
|

Conjugates of several lupane, oleanane, and ursane triterpenoids with the antituberculosis drug isoniazid and pyridinecarboxaldehydes

Abstract: Conjugates of betulinic, oleanolic, ursolic, and glycyrrhetic acids and several of their derivatives with the antituberculosis drug isoniazid and 3-and 4-pyridinecarboxaldehydes were synthesized.Betulinic, oleanolic, ursolic, and glycyrrhetic acids have been successfully modified in the last decades to produce new biologically active compounds [1-6] of various structures including hydrazides and hydrazones [4] with antiviral and antitumor activity. It was shown recently that functionalization of the diterpenoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…To our knowledge, UA or OA having a C3 carbonyl and C28 carboxyl groups have not been assayed against any bacterial species, even though both have been used as a starting material in studies of related derivatives against Mycobacterium tuberculosis [39] , S. aureus and Klebsiella pneumoniae [40] . It would be highly interesting to investigate their antibacterial properties to further evaluate the hypothesis of favouring effect of both C3 carbonyl and C28 carboxyl groups in pentacyclic triterpenes.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, UA or OA having a C3 carbonyl and C28 carboxyl groups have not been assayed against any bacterial species, even though both have been used as a starting material in studies of related derivatives against Mycobacterium tuberculosis [39] , S. aureus and Klebsiella pneumoniae [40] . It would be highly interesting to investigate their antibacterial properties to further evaluate the hypothesis of favouring effect of both C3 carbonyl and C28 carboxyl groups in pentacyclic triterpenes.…”
Section: Resultsmentioning
confidence: 99%
“…The solvents were purified and 3-oxo-, 3-oximino-triterpenoids were synthesized according to the standard methods. Compounds 5 , 6 , 25 , and 26 [ 65 ], 8 and 28 [ 66 ], 2,3-indole derivatives of compounds 3, 4 [ 67 ], and 15 [ 68 ] were obtained according to the methods described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Recently we have showed that triterpenoids with A-ring azepano- and hydrazido-, hydrazono-substituents are an important group of derivatives with antibacterial activities [ 22 25 ]. To compare the influence of substituents in different positions of the triterpene core on antibacterial, fungicidal, and antiviral activities, a series of previously synthesized compounds 1–22 (Fig.…”
Section: Resultsmentioning
confidence: 99%